2021
DOI: 10.3389/fmicb.2021.743512
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant-Associated Bacteria, Fungi, and Viruses in Drought Stress Mitigation

Abstract: Drought stress is an alarming constraint to plant growth, development, and productivity worldwide. However, plant-associated bacteria, fungi, and viruses can enhance stress resistance and cope with the negative impacts of drought through the induction of various mechanisms, which involve plant biochemical and physiological changes. These mechanisms include osmotic adjustment, antioxidant enzyme enhancement, modification in phytohormonal levels, biofilm production, increased water and nutrient uptake as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 242 publications
0
41
0
Order By: Relevance
“…Moreover, endophytic microorganisms that promote plant development are also known for their role as drought-tolerance enhancers, which show a variety of strategies for dealing with the effects of drought on plants and soil through modulating the physiological, biochemical, and molecular changes in the plant. These microbes influence plants through the following mechanisms: (1) Alteration in phytohormonal activity; (2) generation of aminocyclopropane-1-carboxylate deaminase (ACCd) to minimize ethylene levels in roots; (3) deposition of osmolytes that impart drought resistance in plants; (4) exopolysaccharide (EPS) manufacturing; (5) microbial volatile organic compounds (mVOCs) generation; (6) antioxidant defense [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, endophytic microorganisms that promote plant development are also known for their role as drought-tolerance enhancers, which show a variety of strategies for dealing with the effects of drought on plants and soil through modulating the physiological, biochemical, and molecular changes in the plant. These microbes influence plants through the following mechanisms: (1) Alteration in phytohormonal activity; (2) generation of aminocyclopropane-1-carboxylate deaminase (ACCd) to minimize ethylene levels in roots; (3) deposition of osmolytes that impart drought resistance in plants; (4) exopolysaccharide (EPS) manufacturing; (5) microbial volatile organic compounds (mVOCs) generation; (6) antioxidant defense [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dissecting the rhizosphere bacterial and fungal communities, their functional roles, and their interactions with the plant hosts are crucial to developing future methods to improve drought tolerance and plant productivity. The root-associated microbes can elevate the drought tolerance mechanisms in plants through the physiological and biochemical pathways in the plants ( 18 ). Plant-microbe interactions in the rhizosphere have been shown to enhance host resistance to environmental stress and support plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-microbe interactions in the rhizosphere have been shown to enhance host resistance to environmental stress and support plant growth. Some of these plant-associated microbial mechanisms include biofilm formation ( 19 ), osmotic adjustments ( 20 ), changes in phytohormonal levels ( 18 ), increase in antioxidant enzymes ( 18 ), increase in nutrient and water uptake ( 21 , 22 ), and optimization of gas exchanges ( 21 , 23 ). Climate change, characterized by rising temperature and shifted precipitation patterns, has caused the increase in drought frequency ( 24 , 25 ) and severity ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a clear contribution from plant-associated microbial members to plant growth and resilience during drought conditions [17][18][19]. Plant growth-promoting bacteria (PGPB) reportedly enhance plant growth during drought [20,21], an observation attributed to the microbial nitrogen cycling and transformation in soil [22].…”
Section: Introductionmentioning
confidence: 99%